Menjaga warisan budaya identitas nasional dalam konteks modern - Alfiansyah, M. Rifky Putra (Maliki Interdisciplinary Journal, 2025)
Cultural heritage is an important foundation in the formation of a nation's national identity. In this era of rapid globalization and modernization, traditional values ​​and local wisdom are often displaced by the flow of globalization culture which is very diverse. This article discusses the role of cultural heritage as a guardian of national identity and the challenges faced in preserving it amidst today's social and technological dynamics. Through an analytical and policy approach, this study can highlight the importance of cooperation between the government, society, and educational institutions in efforts to preserve culture. The results of this study indicate that the preservation of cultural heritage not only plays a role in maintaining national identity, but also becomes a strategy of strength in international culture. Therefore, a strategy is needed that is able to practice traditional cultural values ​​​​in the context of modern life without losing its original basis.